Depiction of Shiva - Temples of India Project Team (Jio Institute, 2024)
Shiva is portrayed with a jatamukuta (crown of matted hair), wielding a trishula (trident) and a sarpa (snake) in the upper hands, and a bijapuraka in the lower left hand, while making the varada hasta (boon-giving gesture) with his lower right hand. One of the Shiva figures is seated, holding the same attributes.